Consumer choices regarding genome-edited food crops: lessons from Japan - Ishii, Tetsuya (Frontiers in Genome Editing, 2025)
Japan has rapidly deregulated certain types of agricultural genome editing, yet the societal integration of these products warrants further investigation. This paper analyzed the sale and people’s perception of genome-edited food crops in Japan after reviewing the regulatory framework. Of four genome-edited crops approved as non-genetically modified organism, only one is sold online to consumers who credit safety information and perceive usefulness. Some consumers express deep safety concern, advocating mandatory labeling. The majority of people are not sufficiently aware of genome editing. To enhance informed consumer choices of genome-edited food crops, it is crucial to share visions in society, hold risk communication for mutual understanding, and maintain clear labels, including organic food standards.